If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3 + c) = 2(c + 4) (3 * 3 + c * 3) = 2(c + 4) (9 + 3c) = 2(c + 4) Reorder the terms: 9 + 3c = 2(4 + c) 9 + 3c = (4 * 2 + c * 2) 9 + 3c = (8 + 2c) Solving 9 + 3c = 8 + 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. 9 + 3c + -2c = 8 + 2c + -2c Combine like terms: 3c + -2c = 1c 9 + 1c = 8 + 2c + -2c Combine like terms: 2c + -2c = 0 9 + 1c = 8 + 0 9 + 1c = 8 Add '-9' to each side of the equation. 9 + -9 + 1c = 8 + -9 Combine like terms: 9 + -9 = 0 0 + 1c = 8 + -9 1c = 8 + -9 Combine like terms: 8 + -9 = -1 1c = -1 Divide each side by '1'. c = -1 Simplifying c = -1
| y=200+20x | | 90+x+23+3x+27=180 | | 5x-4=-6x-15 | | (2x-8)/-5=9 | | 10(x+8)=100 | | 9x-2/5 | | 4(-3x-10)=2(x+8) | | (2x-8)/-5=0 | | 7x-18=6x+3 | | 5(g-2)+6=6(g-4) | | 5(u+8)=7u+34 | | 4(c+2)=7c+4-3c+4 | | 3w-3x-y+6w+15x-7y= | | 1/3q-6=3 | | 40-5x=5(-5x+4) | | 3-10k=-3(5k+2) | | x^6+5=10 | | 5c+30c-2=7(5c+8) | | 8x-3y+13w-5y-4w+4x= | | 12+14=2x | | 80+2x+10+3x+10=180 | | y=12x^2+6x-6 | | 3z+2i=1+2z+1+i | | 3-10k=-2(5k+2) | | 3y+2x=4.9 | | 135+x+2+15=180 | | 7(4d-6)= | | x+x+x+y=4.9 | | 8d+6d=14 | | 5*260/30 | | 6w+3y+4x+8x-11y+4w= | | x^2+10x-e^4=0 |